2021
DOI: 10.1021/acsorginorgau.1c00007
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Driven C–S Bond Formation Based on Electron Donor–Acceptor Excitation and Hydrogen Atom Transfer Combined System

Abstract: Developed herein is a visible-light-driven synthesis of sulfides by an electron donor–acceptor/single electron transfer and hydrogen atom transfer combined system without transition metals and strong oxidants. This reaction proceeds through the excitation of an electron donor–acceptor complex between a thiolate and an aryl halide, followed by the hydrogen atom transfer from an alkane to the generated aryl radical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 54 publications
4
29
0
Order By: Relevance
“…Given previous reports, [3a–b] especially the thioetherification described by Bunnett et al., [13a] and the mechanistic findings described herein, a plausible mechanism for this C(sp 2 )−S coupling is proposed in Figure 2E. The proposed mechanism involves the formation of an intermediate EDA complex that induces a unimolecular nucleophilic substitution (S RN 1) radical chain.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…Given previous reports, [3a–b] especially the thioetherification described by Bunnett et al., [13a] and the mechanistic findings described herein, a plausible mechanism for this C(sp 2 )−S coupling is proposed in Figure 2E. The proposed mechanism involves the formation of an intermediate EDA complex that induces a unimolecular nucleophilic substitution (S RN 1) radical chain.…”
Section: Resultssupporting
confidence: 68%
“…On the other hand, an examination of various inorganic and organic bases revealed that carbonates and potassium phosphate tribasic prove to be suitable bases for this thioetherification reaction. The less expensive K 2 CO 3 ($ 0.08/gram) gave better results than Cs 2 CO 3 ($ 3.78/gram), which had been used in other reported EDA complex thioetherifications [3a–b] . Notably, an open‐to‐air experiment afforded identical results to those found under inert atmosphere, indicating that oxygen did not affect the transformation (entry 9).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Upon publication of the original article, the authors became aware of another work in this area that reported a related transformation, given below as ref. 1 .…”
mentioning
confidence: 99%